Influence of a High Degree of Filling on the Properties of Pozzolanic Cement - A.I., Buriev; M.I., Iskandarova; G.B., Begjanova (RA Journal of Applied Research, 2023)
Slagash wastes of the Angren and Novo–Angren TPPs of dry selection high pozzolanic and hydraulic activity and its compliance with the requirements for State Standard of the Republic of Uzbekistan 901 for active mineral additives have been established, and therefore, it is recommended as an active mineral additive for the production of pozzolanic cements with a high degree of filling. Replacing from 25% to 50% of high–temperature portland cement clinker with dry–selection composite ash and slag waste ensures the production of pozzolanic cement grades 400–500. Concretes based on pozzolanic cements with a high content of СASW show a fairly high resistance to the aggression of sulfate salts, frost and changes in atmospheric vibrations, which makes the developed cements in demand in the construction industry of the Republic.